Is periodontal disease a risk indicator for urogenital cancer? A systematic review and meta-analysis of cohort studies - Li, Weiqi; Wang, Simin; He, Yuhan; Zhang, Yongshang; Lin, Shanfeng; Cen, Dongdong; Lin, Li (Frontiers in Oncology, 2022)
Objectives: The objective of the present work was to conduct a systematic review and meta-analysis to assess the association between periodontal disease (PD) and urogenital cancer (UC) risk. Materials and Methods: An electronic search in PubMed, EMBASE, the Cochrane Library, and Web of Science was conducted using MeSH terms to identify cohort studies published before May 17, 2022. Cohort studies examining the association between PD and UC risk were included. We used a random-effects model to summarize the effect sizes with 95% confidence intervals (CIs) of the included studies with PD as the indicator and UC as the outcome. Results: Eleven cohort studies met the inclusion criteria. Our results suggest that PD patients increases the risk of UC by 1.24-fold (hazard ratio (HR), 1.24; 95% CI, 1.17-1.31; I2, 22.4%). The strength of the sensitivity analysis and cumulative meta-analysis confirmed the reliability of the results. Conclusion: We found that PD is a potential risk factor for UC. Our results indicate that along with the decrease in the incidence of PD,PD treatment may help prevent UC. We hope that our study will raise awareness of periodontal health, thereby reducing the incidence of UC.